Unraveling the Socioeconomic Characteristics of Lac Growers in Ranchi District of Jharkhand - Sinha, Manjisha; Yogi, R. K.; Vani, N. (Indian Forester, 2020)
The study based on the structured interview was carried out to analyze the socioeconomic characteristics of the people living in and around the forest areas of Bundu, Namk- urn and Angara blocks of Ranchi district in Jharkhand. The data have been obtained from 90 farmers belonging to six villages using multistage random sampling technique. The households were classified using the sturge* formula depending on the lac host trees available for lac production. The result indicated the prevalence of small and marginal farmers involved mostly in dryland cultivation. The resource endowment in terms of the available host trees for lac cultivation varies from 29 to 80 trees but the utilization pattern varies from 48.27 per cent to 62 per cent across different categories of the household. The educational level was low as most of the family members have completed secondary level; the educational attainment of head of the household was lowest in case of small lac growers and was highest in very large categories. The educational attainment of lac growers justifies the lower level of host utilization pattern across different households. In order to increase the lac production, it is required to increase the utilization pattern among the lac growers in the state which could be increased through providing training and field demonstrations to lac farmers.